High life satisfaction reported among small-scale societies with low incomes - Galbraith, E. D.; Barrington-Leigh, C.; Miñarro, S.; Álvarez-Fernández, S.; Attoh, Emmanuel M. N. A. N.; Benyei, P.; Calvet-Mir, L.; Carmona, R.; Chakauya, R.; Chen, Z.; Chengula, F.; Fernández-Llamazares, Á.; et al. (Proceedings of the National Academy of Sciences, 2024)
Global polls have shown that people in high-income countries generally report being more satisfied with their lives than people in low-income countries. The persistence of this correlation, and its similarity to correlations between income and life satisfaction within countries, could lead to the impression that high levels of life satisfaction can only be achieved in wealthy societies. However, global polls have typically overlooked small-scale, nonindustrialized societies, which can provide an alternative test of the consistency of this relationship. Here, we present results from a survey of 2,966 members of Indigenous Peoples and local communities among 19 globally distributed sites. We find that high average levels of life satisfaction, comparable to those of wealthy countries, are reported for numerous populations that have very low monetary incomes. Our results are consistent with the notion that human societies can support very satisfying lives for their members without necessarily requiring high degrees of monetary wealth.